2014
DOI: 10.1097/brs.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Planning and Neurological Outcome After Anterior Approach to Remove a Disc Herniation at the C7–T1 Level in 19 Patients

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Falavigna et al 4) recommended against the use of standalone cages alone at the C7-T1 level because of the risk of cage displacement by extrusion. They reported that 2 of 10 patients with stand-alone cages required reoperation for extrusion of the cage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Falavigna et al 4) recommended against the use of standalone cages alone at the C7-T1 level because of the risk of cage displacement by extrusion. They reported that 2 of 10 patients with stand-alone cages required reoperation for extrusion of the cage.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, access to C7-T1 disc herniations through the anterior aspect may be difficult because of restrictions caused by imposed obstructions by bone structures, the slope of the vertebral bodies, and the vital structures. However, reports in the literature regarding the anterior approach for C7-T1 disc herniation are few 4 8) . Thus, we report our experience with the anterior approach for the treatment of C7-T1 disc herniation, with regard to clinical presentation, limitations of operative exposure, and neurological outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of patients in all the included studies was 419; 234 were males (55.8%) and 185 were females (44.2%). The average age of all patients was 47 years, with the youngest mean age being 28.1 years in Dalbayrak et al 14 and the oldest mean age 63 years in Falavigna et al 19 The average follow-up time of all patients was 40 months. The summary of patients and study characteristics is shown in Table 1.…”
Section: Patients and Study Characteristicsmentioning
confidence: 94%
“…Anterior cervical decompression and fusion (ACDF) is an effective treatment for many patients with pathology at C7-T1 [1] , [2] , [4] , [5] , [6] . There is little data regarding the results of cervical disc replacement (CDR) at the cervicothoracic junction.…”
Section: Introductionmentioning
confidence: 99%